Efeitos de sentido da proposta curricular de Santa Catarina no discurso de professores e alunos de 5ª e 6ª série de uma escola estadual de Santa Catarina - D'Alascio, Miriam Gomes (2008)
This study is part of a Discourse Analysis Project carried out by Unisul faculty and students known as “Grupo de Análise do Discurso – Pesquisa e Ensino” (GADIPE), which focuses mainly on the Curriculum Proposal of Santa Catarina (1998, 2005). Starting from the discourse contained in that document, this study is intended to analyze the principles, contents, and methodology involved in the social reality and how the teaching/learning process unfolds, considering the relationship between teacher-student and student-student taking place in teaching Portuguese language classes. Discourse Analysis (DA) having Bakhtin (language philosophy) and Vygotsky (learning and development) as mentors was used as theoretical basis, associated with the Curriculum Proposal of Santa Catarina theoretical groundings. This study seeks to identify how teachers deal with new technologies and how they build up knowledge and make their choices in daily classroom practice. Therefore, it is important to discuss their theory and practice as a two-faced controversial reality. The goal of this study is to confront the built-up meanings of the discourse in the Curriculum Proposal with the discourses of teachers and students who are interlocutors and agents in this process. In this confrontation, the proximity and the distance of the agents and their respective discourses will be shown. It will also be possible to identify which elements of the content demand deeper reflection and further theoretical and methodological study.